1999
DOI: 10.1002/1531-8249(199905)45:5<611::aid-ana9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to sporadic Parkinson's disease by a certain combined ?-synuclein/apolipoprotein E genotype

Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative disorders affecting about 1% of Western populations older than age 50. The pathological hallmark of PD are Lewy bodies, that is, intracytoplasmic inclusion bodies in affected neurons of the substantia nigra. Recently, α‐synuclein (α‐SYN) has been identified as the main component of Lewy bodies in sporadic PD, suggesting involvement in neurodegeneration via protein accumulation. The partially overlapping pathology of PD and Alzheimer's disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
3
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(168 citation statements)
references
References 37 publications
4
157
3
4
Order By: Relevance
“…Families with mutated α-syn exhibit autosomal dominant PD (Athanassiadou et al, 1999;Kruger et al, 1998;Polymeropoulos et al, 1997;Zarranz et al, 2004), and gene multiplication leading to increased wildtype α-syn levels also causes disease (Singleton et al, 2003). Certain α-syn promoter polymorphisms are PD risk factors, suggesting that even modest increases in expression can predispose to disease (Farrer et al, 2001;Kruger et al, 1999;Pals et al, 2004;Tan et al, 2000;Wang et al, 2006). In patients without genetic mutations, α-syn is found in Lewy bodies and degenerating neurites (Irizarry et al, 1998;Spillantini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Families with mutated α-syn exhibit autosomal dominant PD (Athanassiadou et al, 1999;Kruger et al, 1998;Polymeropoulos et al, 1997;Zarranz et al, 2004), and gene multiplication leading to increased wildtype α-syn levels also causes disease (Singleton et al, 2003). Certain α-syn promoter polymorphisms are PD risk factors, suggesting that even modest increases in expression can predispose to disease (Farrer et al, 2001;Kruger et al, 1999;Pals et al, 2004;Tan et al, 2000;Wang et al, 2006). In patients without genetic mutations, α-syn is found in Lewy bodies and degenerating neurites (Irizarry et al, 1998;Spillantini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Four of them showed that the E4 allele occurred more often in demented 105,106 and nondemented 107,108 PD patients, but the others did not find any positive associations. 69, Two additional studies examined the C/G-T/A transition converting codon 158 from arginine (E3) to cysteine (E2), and found that E4 allele E4 had a higher frequency in young 131 and demented 132 PD patients. Taken together, the results of these studies raise doubts as to the association between Apo-E and PD risk.…”
Section: N-acetyl Transferasementioning
confidence: 99%
“…Mutations of the alphasynuclein gene have been shown to be relevant in some rare cases of autosomal dominant PD. Among the nine association studies performed to date, only four found significant results for the polymorphism of the promoter region of the alpha-synuclein gene (NACP-Rep1) in German, 131 American, 150,151 and Japanese 152 populations; the remaining studies from Japan, 153 Ireland, 154 Singapore, 155 Germany, 156 and Italy 157 found no differences from controls. More studies and meta-analysis are needed in order to determine Polymorphism in dopamine-related genes Y Gilgun-Sherki et al unequivocally whether the alpha-synuclein gene polymorphism is associated with IPD risk (see also Table 1).…”
Section: Linkage-derived Candidate Genesmentioning
confidence: 99%
“…Rare forms of PD are transmitted in an autosomal dominant or autosomal recessive mode of inheritance: for these, mutations in the Park 1 locus (␣-synuclein) or the Park 2 locus have been demonstrated, while the underlying mutation in a third locus, Park 3, has not yet been identified. 1 The vast majority of PD cases, however, are sporadic and are probably caused by the interaction of several genes with multiple environmental factors. One of these genes may be the ⑀4 allele of the apolipoprotein E gene, which in conjunction with a Park 1 promoter polymorphism has very recently been shown to increase the risk for developing sporadic PD.…”
Section: Idiopathic Parkinson's Disease (Pd) Is a Common Neurodegenermentioning
confidence: 99%
“…One of these genes may be the ⑀4 allele of the apolipoprotein E gene, which in conjunction with a Park 1 promoter polymorphism has very recently been shown to increase the risk for developing sporadic PD. 1 The most striking symptoms of PD relate to the motor system, with rigidity, tremor, and akinesia. However, psychiatric manifestations including depression and dementia syndrome are common in PD patients.…”
mentioning
confidence: 99%